Veiklos tyrimas organizacijoje. Socialinių paslaugų senyvo amžiaus žmonėms atvejis Action research in organizations. The case of social services for older adults - Genevičiūtė-Janonienė, Giedrė (Vytautas Magnus University, 2016)
The aim of the study presented in the monograph is to reveal peculiarities, methodological strengths and limitations of participatory action research (PAR) in social service organizations. PAR is analysed as a methodological approach which involves scholars and research participants into a process of reflection, knowledge production and construction of new meanings. PAR application area is quite broad - this strategy is applied in communities, business, education, health and welfare organizations in order to increase involvement of citizens as well as their empowerment in communities and organizations. While highlighting originality and singularity of PAR in organizations, authors of the study discuss notions, definitions and distinctive features of PAR. The scholars distinguish novelty, empowering nature, methodological nuances and criticism toward PAR. The monograph presents models, the process, and stages of PAR. Based on PAR implementation in social service organizations, a need for movement from action to reflection and empowerment of research participants to take the responsibility of the changes in organizations is emphasized. The research sheds a light on psychosocial functioning of organizations as well as their readiness for change. Results and insights drawn by the research create preconditions to increase efficiency and effectiveness of organizations. The investigation presented in the monograph was implemented in social service organizations which provide services for the elderly. Lithuanian population is aging, therefore agencies which provide elderly care should be able to respond to changes in the market and satisfy clients` needs. This is relevant for profit organizations and business enterprises which become more active in the social service sector offering their activities for older people. This study presents the situation of older people in European Union and Lithuania. An overview of theoretical resources is carried out by revealing factors of organizational effectiveness and readiness for changes, concepts and typologies of organizational cultures, elements which are related to psychosocial functioning of organizations: job satisfaction, management, conflicts and their solutions, teamwork and stress at work. Recognition which embraces processes on micro, mezzo and macro levels is another concept that is discussed and analysed in the study. The research presented in the monograph included several stages. In the first stage of the research, a qualitative interpretative study was carried out by interviewing representatives of focus group. The researchers disclosed practical experiences, ideas, achievements, challenges and concerns, questions and tensions that arose in the organizations. 4 institutions participated in the research in this stage - 2 public organizations of home care and 2 private organizations of institutional long-term care. In the second stage of the investigation, a quantitative research was conducted to identify tendencies of readiness for change in social service organizations. 401 respondents from municipal and state organizations and 109 respondents from private agencies (510 in total) participated in the survey. In this stage of the research, objectives were: 1) to identify main factors and elements which determine the functioning of public and private agencies for social services; 2) to reveal differences between public and private organizations of social services; 3) to analyse attitude of employees working in public and private organizations toward development of organizations and to evaluate factors which foster agencies' development; 4) to delineate issues which are important and relevant for each organization and its psycho-social functioning. The third stage of the research was dedicated to construct a new knowledge on changes to be initiated in the organizations. 2 case studies were conducted by applying a constructivist version of grounded theory (Charmaz, 2006). The first case study was carried out in municipal organizations of home social services for the elderly. The second case study was conducted in public agencies which provide institutional long-term services for the elderly. The main techniques and methods of this research were individual interviews, interviews with focus groups and group discussions as well as methodological seminars to get a feedback from research participants. Five managers and 38 employees participated in the study. The research has empowered the authors to provide methodological recommendations for the implementation of PAR in organizations. The study actualized principles and elements of successful implementation of PAR in agencies of social services - a need to reflect processes and get a feedback in organizations, foster creativity and reciprocity in relationships between researchers and research participants at organizations, support trust and respect, avoid harm and disrespect.